2004
DOI: 10.1051/vetres:2004005
|View full text |Cite
|
Sign up to set email alerts
|

Survival, immune responses and tissue cyst production in outbred (Swiss white) and inbred (CBA/Ca) strains of mice experimentally infected with Neospora caninum tachyzoites

Abstract: -The present work compared inbred (CBA/Ca) and outbred (Swiss white) strains of mice for their capacity to cope with a Neospora caninum infection and to consistently produce tissue cysts. In each experiment Swiss white and CBA/Ca mice were given three different doses of NC-1 tachyzoites. Lymphoproliferative and humoral responses as well as cytokine production were evaluated eight weeks after infection (PI) whereas tissue cyst production and histopathology were assessed 4, 6 and 10 weeks PI in immunosuppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
14
1
1
Order By: Relevance
“…Coccidia A and B did not cause disease in mice with known susceptibility to T. gondii including B6.129S7- Ifng tm1Ts /J, CBA/CaJ and Swiss Webster (CFW ® ) ( Rytel and Jones, 1966 , Villegas et al., 2002 , Gavrilescu and Denkers, 2003 ). Surprisingly, Coccidia A and B were not pathogenic to CBA/CaJ mice despite previous studies showing that CBA/Ca mice can be used as a model of N. caninum pathogenesis ( McGuire et al., 1997 , Rettigner et al., 2004 ). These findings, taken together with the lack of growth in MA104 cells or reactivity of serum from Coccidia A- and B-infected sea lions with N. caninum , T. gondii or S. neurona antigen by IFAT, is further evidence of the taxonomic divergence of the sea lion parasites from known tissue-cyst forming coccidia with terrestrial life cycles.…”
Section: Discussionmentioning
confidence: 63%
“…Coccidia A and B did not cause disease in mice with known susceptibility to T. gondii including B6.129S7- Ifng tm1Ts /J, CBA/CaJ and Swiss Webster (CFW ® ) ( Rytel and Jones, 1966 , Villegas et al., 2002 , Gavrilescu and Denkers, 2003 ). Surprisingly, Coccidia A and B were not pathogenic to CBA/CaJ mice despite previous studies showing that CBA/Ca mice can be used as a model of N. caninum pathogenesis ( McGuire et al., 1997 , Rettigner et al., 2004 ). These findings, taken together with the lack of growth in MA104 cells or reactivity of serum from Coccidia A- and B-infected sea lions with N. caninum , T. gondii or S. neurona antigen by IFAT, is further evidence of the taxonomic divergence of the sea lion parasites from known tissue-cyst forming coccidia with terrestrial life cycles.…”
Section: Discussionmentioning
confidence: 63%
“…It has been suggested that the immune response in inbred mice is significantly different from that of outbred mice (23) (affecting, for example, CD8 + T cell responses to bacterial infection [24]). We thus investigated whether our infection model could be applied to inbred C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that vaccination of naïve cows with live tachyzoites was protective against experimental challenge (Williams et al, 2007;Rojo-Montejo et al, 2013;Weber et al, 2013;Hecker et al, 2013;Reichel et al, 2014;Monney and Hemphill, 2014). The Israeli N. caninum NcIs491 isolate, obtained from brain tissue of an aborted fetus, can be easily grown in culture and is suggested to be of low pathogenicity to laboratory animals including gerbils (Fish et al, 2007) and mice (unpublished results), in comparison with the NC-1 strain (Lindsay et al, 1995;Rettigner et al, 2004).…”
Section: Introductionmentioning
confidence: 91%